Proof of concept study with an HER-2 mimotope anticancer vaccine deduced from a novel AAV-mimotope library platform. (2nd July 2016) - Singer, Josef; Manzano-Szalai, Krisztina; Fazekas, Judit; Thell, Kathrin; Bentley-Lukschal, Anna; Stremnitzer, Caroline; Roth-Walter, Franziska; Weghofer, Margit; Ritter, Mirko; Pino Tossi, Kerstin; Hörer, Markus; Michaelis, Uwe; et al.
ABSTRACT: Background : Anticancer vaccines could represent a valuable complementary strategy to established therapies, especially in settings of early stage and minimal residual disease. HER-2 is an important target for immunotherapy and addressed by the monoclonal antibody trastuzumab. We have previously generated HER-2 mimotope peptides from phage display libraries. The synthesized peptides were coupled to carriers and applied for epitope-specific induction of trastuzumab-like IgG. For simplification and to avoid methodological limitations of synthesis and coupling chemistry, we herewith present a novel and optimized approach by using adeno-associated viruses (AAV) as effective and high-density mimotope-display system, which can be directly used for vaccination.Methods : An AAV capsid display library was constructed by genetically incorporating random peptides in a plasmid encoding the wild-type AAV2 capsid protein. AAV clones, expressing peptides specifically reactive to trastuzumab, were employed to immunize BALB/c mice. Antibody titers against human HER-2 were determined, and the isotype composition and functional properties of these were tested. Finally, prophylactically immunized mice were challenged with human HER-2 transfected mouse D2F2/E2 cells.Results : HER-2 mimotope AAV-vaccines induced antibodies specific to human HER-2. Two clones were selected for immunization of mice, which were subsequently grafted D2F2/E2 cells. Both mimotope AAV clones delayed the growth of tumors significantly, as compared to controls.Conclusion : In this study, a novel mimotope AAV-based platform was created allowing the isolation of mimotopes, which can be directly used as anticancer vaccines. The example of trastuzumab AAV-mimotopes demonstrates that this vaccine strategy could help to establish active immunotherapy for breast-cancer patients.